Synthesis and broad-spectrum antiproliferative activity of diarylamides and diarylureas possessing 1,3,4-oxadiazole derivatives - El-Din, Mahmoud M. Gamal; El-Gamal, Mohammed I.; Abdel-Maksoud, Mohammed S.; Yoo, Kyung Ho; Oh, Chang-Hyun (Pergamon Press Ltd., 2015)
A series of diarylamides and diarylureas possessing 1,3,4-oxadiazole scaffold was designed and synthesized. Their in vitro antiproliferative activities were tested against a panel of 58 cell lines of nine different cancer types at the NCI, and compared with Sorafenib as a reference compound. Most of the compounds showed strong and broad-spectrum antiproliferative activities. The diarylurea compound 2g possessing 4-chloro-3-(trifluoromethyl) phenyl terminal moiety showed the highest mean % inhibition value of about 100% over the 58-cell line panel at 10 mu M concentration. Also compounds 2h, 2l, 2m exhibited mean % inhibition over 90% at 10 mu M concentration. The IC50 value of compound 2b over SNB-75 CNS cancer cell line was 0.65 mu M. Compound 2h also exerted submicromolar IC50 values of 0.67, 0.80, and 0.87 mu M against PC-3 prostate cancer cell line, HCT-116 colon cancer cell line, and ACHN renal cancer cell line, respectively. Compound 2h showed comparable efficacy to Sorafenib. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: MELANOMA-CELL LINE; BIOLOGICAL EVALUATION; ANTICANCER AGENTS; 1,3,4-TRIARYLPYRAZOLE SCAFFOLD; BEARING OXADIAZOLE; KINASE INHIBITION; MOLECULAR DOCKING; DESIGN; NUCLEUS; MOIETY